Las empresas ante su desafío histórico: de la acumulación egoísta a la responsabilidad social - Dejo, Federico (2005)
When the first productive organizations of the pre-industrial era appeared, man noticed that the development of these organizations had a negative impact, especially in terms of labor exploitation. However, man also foresaw the positive impacts: wealth and diversity of goods and products. This led later on, to the discussion of which role the companies must play inthe development of society. Socialist movements and subsequent revolutions tried to eradicate labor exploitation within the corporate world. But socialism’s failure to eliminate social injustice only strengthened the capitalist model. The manner in which most companies perform their activities, based solely on profit, threatens to eradicate not only wage earners, but theplanet it self. As a response to this, the concept of Socially Responsible Companies (SRC),emerging with great strength in the past decade, constitutes a rational and viable alternative in order to achieve a sustainable, desirable and necessary type of development.